Digital, ethical, political: Network time and common responsibility. (July 2018) - Hassan, Robert
The essay argues that a proper ethical foundation for the political processes underlying liberal democracy is unattainable in a globalized society made possible through networked computers – and the transformed relationship with temporality that is generated by them. The essay brings together the computer ethics of Norbert Wiener and the temporal ethics of Hans Jonas to show that both original visions for a better world are unrealizable in the unanticipated context of what is termed 'network time'. The essay argues further that to develop an ethical basis for liberal democracy, digital logic and its effects must be contrasted with that which they ceaselessly colonize and marginalize today: an irreducibly analogue world, with analogue politics, analogue technologies and analogue humans who conceived and developed liberal democracy as a cornerstone of the project of Enlightenment. Through contrast and critique, the essay reveals the difficulty for any ethico-political project within the digital and argues that the present post-modern relationship with computing, in which 'market forces' determine technological forms and applications, is socially destructive and must be brought under a new aegis of democratic and common responsibility.